Pengolahan Camilan Stick Rumput Laut Hijau (Eucheuma) Berdasarkan Uji Organoleptik pada Murid Sekolah Dasar (SD) Negeri 29 Kendari - Ellyani Abadi; Riska Mayangsari; Siti Hadrayanti Ananda; Siti Umrana; Jenny Qlifianti Demmalewa (Universitas Batanghari Jambi, 2023)
Stick snack products are foods that are still rarely found in the community. Green seaweed plants contain carbohydrates, protein, fat, most of which are salt, sodium, and potassium compounds. beta-carotene and minerals. This study aims to determine the acceptability of color, texture, aroma and taste of green seaweed stick snacks with the addition of wheat flour in school children at SDN 29 Kendari. The type of research used is descriptive. The panelists were 53 students of SD Negeri 29 Kendari. The sampling technique used is the saturated survey. The data obtained using observation sheets and analyzed descriptively. The result of color preference for green seaweed stick snack products, namely R4 has the best acceptance rate of 90.6%. From the aspect of texture, that is R4 as much as 89.2%. From the aspect of aroma, namely R4 as much as 92.5%. Meanwhile, from the taste aspect, R4 is 92.5%. The conclusion of this study is the acceptability of green seaweed stick snacks based on the attributes of color, texture, aroma and taste. Meanwhile, the panelists preferred the R4 product more than other products.